Metode Keteladanan Guru Pendidikan Agama Islam dalam Meningkatkan Akhlakul Karimah Pada Peserta Didik MTs Al-Falah Sinar Gunung dan MTs Mathla’ul Anwar Lansbaw Kabupaten Tanggamus - Lestari, Andika; Fakhri, Jamal; Abbas, Erjati (Attractive : Innovative Education Journal, 2024)
The aim of this research is to identify and analyze exemplary values, application, results, supporting and inhibiting factors, from the application of exemplary values ??by Islamic teachers in forming good morals at MTs Al-Falah Sinar Gunung and MTs Mathlaul Anwar Lansbaw, Tanggamus Regency. This research uses a qualitative approach with descriptive methods. The data collection techniques are observation, interviews and documentation. So the data collected is analyzed using data reduction steps, data display. The results of the research show that by applying example, teachers are able to improve and shape the al-karimah morals of students at MTs Al-Falah Sinar Gunung and MTs Mathlaul Anwar Lansbaw, Tanggamus Regency Keywords: Islamic Education, Teaching, Akhlakul Karimah